ANALISIS PEMANFAATAN OPAC SEBAGAI SARANATEMU KEMBALI INFORMASI DI PERPUSTAKAAN UIN RADEN FATAH PALEMBANG - Anggraini, Diah (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This research is titled analysis of OPAC utilization as a means of guest return information at UIN Raden Fatah Library Palembang. The purpose is to find out the utilization of OPAC as a means of guest return information at UIN Raden Fatah Library Palembang. Since around 2015, visitors have been utilizing the library's Online Public Access Catalog (OPAC). The purpose of this survey is to collect data on the frequency of visitors to UIN Raden Fatah Library in utilizing the library's online public access catalog (OPAC). This test can be considered an emotional intelligence quiz whose final score is most significant. The value of a program is measured by analyzing its cumulative impact. This research shows that OPAC is widely used by library patrons. Patrons can use the OPAC without worrying about overdue fees. Patrons get tremendous help in finding varieties quickly, thus saving the time they spend searching.